'There's only so much an individual can do': an ecological systems perspective on mental health and wellbeing in the early stages of doctoral research. Issue 7 (9th August 2022) - Jackman, Patricia C.; Sanderson, Rebecca; Allen-Collinson, Jacquelyn; Jacobs, Lisa
ABSTRACT: Calls to address concerning evidence surrounding mental health and wellbeing in doctoral researchers have grown internationally in recent years. Adopting an ecological systems approach, this article explores doctoral researchers' perspectives on what influences mental health and wellbeing in early-stage doctoral research. Forty-seven doctoral researchers took part in focus groups exploring mental health and wellbeing in the first year of doctoral study. The framework generated through our thematic and connecting analyses emphasises the interdependency of the various layers of the environment surrounding early-stage doctoral researchers. In line with our theoretical perspective, we describe the influence of: individual factors; the microsystem; the mesosystem; the exosystem; and the macrosystem. Participants highlighted the impact of the broader working culture in academia on their mental health and wellbeing, which permeated other, more proximal layers within their environment. This article contributes knowledge that can aid the development of interventions seeking to support mental health and wellbeing in doctoral researchers. Furthermore, our findings suggest that without the adoption of a whole-systems approach, efforts to improve mental health and wellbeing in these researchers could be difficult.